Digitalization is not gender-neutral - Genz, Sabrina; Schnabel, Claus (Economics letters, 2023)
Using unique linked employer-employee data for Germany and a matching approach, we provide novel insights on the individual-level employment effects of digitalization. We show that the first-time introduction of digital technology in an establishment affects women more strongly than men. This holds both in terms of lower days employed and higher days unemployed. We find that employment losses are largest for individuals conducting non-routine tasks, and again it is women who suffer the most. Our insights imply that digitalization is not gender-neutral, suggesting that it is important to avoid a gender bias in technological progress.
CRIS-Team Scopus Importer:2023-08-04
Keywords: Digitalization; Employment; Gender; Separations; Tasks